2016
DOI: 10.1073/pnas.1606101113
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient ratios in pollen shape bumble bee ( Bombus impatiens ) foraging strategies and floral preferences

Abstract: To fuel their activities and rear their offspring, foraging bees must obtain a sufficient quality and quantity of nutritional resources from a diverse plant community. Pollen is the primary source of proteins and lipids for bees, and the concentrations of these nutrients in pollen can vary widely among host-plant species. Therefore we hypothesized that foraging decisions of bumble bees are driven by both the protein and lipid content of pollen. By successively reducing environmental and floral cues, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
327
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 311 publications
(339 citation statements)
references
References 78 publications
10
327
0
2
Order By: Relevance
“…Furthermore, bumble bee colonies will increase their foraging efforts to higher quality pollen (or nectar), or reduce foraging efforts to low‐quality pollen, even if no alternative is available (Dornhaus & Chittka, 2001, 2004; Kitaoka & Nieh, 2008). Our previous research revealed that B. impatiens , when collecting pollen for their colony in an enclosed outdoor foraging‐arena, preferred host‐plant species with pollen of high protein:lipid, or P:L ratios (~5:1 P:L, which was the maximum for the plant species in this study; Vaudo, Patch, Mortensen, Tooker, & Grozinger, 2016). Notably, foragers nearly ignored plant species offering the lowest P:L pollen (0.72:1 P:L), even when abundant pollen was available for collection (Vaudo, Patch et al., 2016).…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Furthermore, bumble bee colonies will increase their foraging efforts to higher quality pollen (or nectar), or reduce foraging efforts to low‐quality pollen, even if no alternative is available (Dornhaus & Chittka, 2001, 2004; Kitaoka & Nieh, 2008). Our previous research revealed that B. impatiens , when collecting pollen for their colony in an enclosed outdoor foraging‐arena, preferred host‐plant species with pollen of high protein:lipid, or P:L ratios (~5:1 P:L, which was the maximum for the plant species in this study; Vaudo, Patch, Mortensen, Tooker, & Grozinger, 2016). Notably, foragers nearly ignored plant species offering the lowest P:L pollen (0.72:1 P:L), even when abundant pollen was available for collection (Vaudo, Patch et al., 2016).…”
Section: Introductionmentioning
confidence: 56%
“…Our previous research revealed that B. impatiens , when collecting pollen for their colony in an enclosed outdoor foraging‐arena, preferred host‐plant species with pollen of high protein:lipid, or P:L ratios (~5:1 P:L, which was the maximum for the plant species in this study; Vaudo, Patch, Mortensen, Tooker, & Grozinger, 2016). Notably, foragers nearly ignored plant species offering the lowest P:L pollen (0.72:1 P:L), even when abundant pollen was available for collection (Vaudo, Patch et al., 2016). Additionally, in the laboratory in the absence of external floral cues and brood, B. impatiens maintained these P:L preferences among pollen from different species and exhibited preferences of 5:1–10:1 P:L from nutritionally modified pollens (Vaudo, Patch et al., 2016).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations